2015
DOI: 10.1371/journal.pone.0134183
|View full text |Cite
|
Sign up to set email alerts
|

Species Delimitation in the Genus Moschus (Ruminantia: Moschidae) and Its High-Plateau Origin

Abstract: The authenticity of controversial species is a significant challenge for systematic biologists. Moschidae is a small family of musk deer in the Artiodactyla, composing only one genus, Moschus. Historically, the number of species in the Moschidae family has been debated. Presently, most musk deer species were restricted in the Tibetan Plateau and surrounding/adjacent areas, which implied that the evolution of Moschus might have been punctuated by the uplift of the Tibetan Plateau. In this study, we aimed to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 58 publications
4
30
0
Order By: Relevance
“…Also, it also includes response to the stimulus (71 genes, GO:0050896), cellular response to stimulus (50 genes, GO:0051716), and many categories related to metabolism. This result is consistent with the biological characteristics of the siberian musk deer, which can especially explain its survivability under extreme conditions and its obvious response and alertness to external stimuli [19,40,66]. The distribution of GO annotations in different functional categories indicated a substantial diversity of DEGs.…”
Section: Differentially Expressed Genes and Functional Enrichment Anasupporting
confidence: 85%
See 2 more Smart Citations
“…Also, it also includes response to the stimulus (71 genes, GO:0050896), cellular response to stimulus (50 genes, GO:0051716), and many categories related to metabolism. This result is consistent with the biological characteristics of the siberian musk deer, which can especially explain its survivability under extreme conditions and its obvious response and alertness to external stimuli [19,40,66]. The distribution of GO annotations in different functional categories indicated a substantial diversity of DEGs.…”
Section: Differentially Expressed Genes and Functional Enrichment Anasupporting
confidence: 85%
“…The second declines occurring between 0.20 to 0.09 Mya, was detected towards and end of the interglacial period (0.13-0.07 Mya), which presented environmental conditions similar to that of the present [64]. The uplift of the Tibetan Plateau, which caused aridification, and desertification that was dramatically enhanced in the middle Pleistocene age, which reduced the habitat of the musk deer, resulting in a decline of population size [40,65]. The Siberian musk deer population size then recovered again between 0.05-0.03 Mya during the greatest lake period (0.03-0.04 Mya) because the glaciations were less extended, weather became warm and the forest had expanded that could have contributed to the population expansion [60][61][62].…”
Section: Genomic Diversity and Demography Inferencementioning
confidence: 79%
See 1 more Smart Citation
“…Hippopotamus amphibius (GenBank: AP003425) and Camelus bactrianus (GenBank: EF507798) were selected as outgroups. The phylograms obtained from BI and ML (data not shown) all strongly indicated that Moschidae was a sister group to Bovidae (Hassanin and Douzery 2003;Yang et al 2013;Pan et al 2015). In Moschidae, our analysis supported that M. berezovskii should be divided into two subspecies, and the captive species was most closely related to the M. anhuiensis and the wild species was most closely related to M. chrysogaster (Su et al 1999;).…”
Section: Mitogenome Announcementmentioning
confidence: 51%
“…All the information about neighbor-joining tree of five pecora families were came from http://ac.els-cdn.com/S1055790399906164/1-s2.0-S1055790399906164-main.pdf?_tid=e6951092-99dc-11e6-959f-00000aab0f02&acdnat=1477308652_8d639676fd40097612c932a0776ec24a . 흑사향노루(黑麝) M. fuscus 는 중국의 운 남, 서장에서만 발견되었다 5,22) . (Table 3, Fig.…”
Section: 학명에 따른 사향의 기원 동물 분류mentioning
confidence: 99%